Escherichia coli ST131 clones harbouring AggR and AAF/V fimbriae causing bacteremia in Mozambican children: Emergence of new variant of fimH27 subclone. - Inácio Mandomando; Delfino Vubil; Nadia Boisen; Llorenç Quintó; Joaquim Ruiz; Betuel Sigaúque; Tacilta Nhampossa; Marcelino Garrine; Sergio Massora; Pedro Aide; Ariel Nhacolo; Maria J Pons; et al. (Public Library of Science (PLoS), 2020)
Multidrug-resistant Escherichia coli ST131 fimH30 responsible for extra-intestinal pathogenic (ExPEC) infections is globally distributed. However, the occurrence of a subclone fimH27 of ST131 harboring both ExPEC and enteroaggregative E. coli (EAEC) related genes and belonging to commonly reported O25:H4 and other serotypes causing bacteremia in African children remain unknown. We characterized 325 E. coli isolates causing bacteremia in Mozambican children between 2001 and 2014 by conventional multiplex polymerase chain reaction and whole genome sequencing. Incidence rate of EAEC bacteremia was calculated among cases from the demographic surveillance study area. Approximately 17.5% (57/325) of isolates were EAEC, yielding an incidence rate of 45.3 episodes/105 children-years-at-risk among infants; and 44 of isolates were sequenced. 72.7% (32/44) of sequenced strains contained simultaneously genes associated with ExPEC (iutA, fyuA and traT); 88.6% (39/44) harbored the aggregative adherence fimbriae type V variant (AAF/V). Sequence type ST-131 accounted for 84.1% (37/44), predominantly belonging to serotype O25:H4 (59% of the 37); 95.6% (35/44) harbored fimH27. Approximately 15% (6/41) of the children died, and five of the six yielded ST131 strains (83.3%) mostly (60%; 3/5) due to serotypes other than O25:H4. We report the emergence of a new subclone of ST-131 E. coli strains belonging to O25:H4 and other serotypes harboring both ExPEC and EAEC virulence genes, including agg5A, associated with poor outcome in bacteremic Mozambican children, suggesting the need for prompt recognition for appropriate management.